2023
DOI: 10.24198/sosiohumaniora.v25i1.41834
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sprirituality and Work Ethic in Improving Work Effectiveness in the Logistics Industry

Abstract: One of the most important elements in any organization is people. With competent human resources, an organization can operate effectively and efficiently. This study aims to measure the role of spirituality and work ethic in improving work effectiveness in the logistics industry. The research method uses quantitative which is descriptive and verifiable. The sample determination technique used is probability sampling type propotional stratified random sampling. The employees sampled were 54 people, out of a pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…So far, no research has been found proving that work effectiveness mediates the influence of workplace spirituality on employees' contextual performance. However, these findings confirm several previous relevant studies which prove that workplace spirituality impacts effectiveness (Daniel, 2010;Kusnadi & Prijono, 2023), work effectiveness affects performance (Arifin & Akhmad, 2022;Arifin & Hidayat, 2023;Rani et al, 2021;Tuffaha, 2020;Assbeihat, 2016;Tsai & Tsai, 2017), and workplace spirituality influences performance (Nwanzu & Babalola, 2021;Jena, 2021;Ekowati, 2022). As shown in testing H3, workplace spirituality has a direct positive effect on employees' work effectiveness.…”
Section: Hypothesis Testingsupporting
confidence: 89%
See 4 more Smart Citations
“…So far, no research has been found proving that work effectiveness mediates the influence of workplace spirituality on employees' contextual performance. However, these findings confirm several previous relevant studies which prove that workplace spirituality impacts effectiveness (Daniel, 2010;Kusnadi & Prijono, 2023), work effectiveness affects performance (Arifin & Akhmad, 2022;Arifin & Hidayat, 2023;Rani et al, 2021;Tuffaha, 2020;Assbeihat, 2016;Tsai & Tsai, 2017), and workplace spirituality influences performance (Nwanzu & Babalola, 2021;Jena, 2021;Ekowati, 2022). As shown in testing H3, workplace spirituality has a direct positive effect on employees' work effectiveness.…”
Section: Hypothesis Testingsupporting
confidence: 89%
“…Meanwhile, work effectiveness is the capacity to select the appropriate course of action in order to achieve a particular objective or set of results, emphasizing those outcomes without considering the costs associated with those outcomes (Alkaf et al, 2021). It also reflected everything related to achieving an organization's target (Kusnadi & Prijono, 2023). Work effectiveness refers to how a person or group performs their primary tasks to achieve the desired goals (Ibrahim & Daniel, 2019).…”
Section: Work Effectiveness and Contextual Performancementioning
confidence: 99%
See 3 more Smart Citations